Closing the water cycle in the agro-industrial sector by reusing treated wastewater for irrigation. (15th October 2017) - Vergine, Pompilio; Salerno, Carlo; Libutti, Angela; Beneduce, Luciano; Gatta, Giuseppe; Berardi, Giovanni; Pollice, Alfieri
Abstract: Reuse of treated wastewater for crop irrigation can contribute to mitigate water stress, especially in Mediterranean countries. The use of reclaimed municipal wastewater for this purpose was demonstrated by numerous studies and full-scale installations. On the other hand, reuse of industrial effluents in irrigation is uncommon and the knowledge in this field is limited. This work aims at assessing the suitability of agro-industrial effluent reuse for irrigation. In the case study presented, a full-scale tertiary treatment based on membrane ultrafiltration and UV disinfection was tested at an agro-industrial site in Apulia (Italy). The wastewater treatment plant processed the stream produced at a vegetable canning factory, and the treated effluents were used for field scale irrigation tests. The variability of wastewater quality and its effects on treatment process performances and reclaimed water quality were investigated. An economic evaluation of the full scale tertiary treatment was also performed. The results showed that the adopted technologies effectively removed suspended solids and the faecal indicator Escherichia coli below the local standards for reuse in irrigation. Furthermore, the use of treated agro-industrial wastewater had no inhibitory effects on the growth of tomato and broccoli, neither resulted in any faecal contamination of crops. In general, the present study shows that reuse of treated wastewater for irrigation is a suitable practice to close the water cycle in the agro-industrial sector. This is very important in areas where the sustainability of agriculture and transformation activities depends on the water available for irrigation. This practice also avoids the discharge of pollutants into water bodies, reducing the environmental impacts of agro-industrial productions. Highlights: Irrigation with treated agro-industrial wastewater is a suitable practice. Treated wastewater had no inhibitory effects on the growth of tomato and broccoli. There were no negative effects on soil salinity and microbial safety of crops. Closing the water cycle in the agro-industry allowed the irrigation of 13 ha. Segregation and separate treatment of heavily polluted fractions may be considered.